Self-assembly of thermo and light responsive amphiphilic linear dendritic block copolymers. (August 2016) - García-Juan, Hugo; Nogales, Aurora; Blasco, Eva; Martínez, Juan Carlos; Šics, Igor; Ezquerra, Tiberio A.; Piñol, Milagros; Oriol, Luis
Graphical abstract: Highlights: Dual responsive amphiphilic linear-dendritic copolymers. Stimuli responsive polymeric vesicles to UV light and temperature. Stimuli induced changes real time monitored by SAXS and WAXS. Polymeric carriers for on demand release of hydrophobic and hydrophilic molecules. Abstract: The synthesis and structural characterization of a new dual responsive linear-dendritic block copolymer (LDBC) is presented. The LDBC is constituted by a thermoresponsive linear block from polymethacrylate of oligo- and diethylene glycol, and a light responsive dendron block of bis-MPA decorated at the periphery with 4-isobutyloxyazobenzene and alkyl chains in a 50:50 M ratio. Blocks are coupled together by copper(I) catalyzed alkyne–azide cycloaddition (CuAAC). The ability of the LDBC to form vesicle self-assemblies in water is described, as well as the effect of light and temperature on the vesicles morphology, on the basis of transmission electron microscopy (TEM), dynamic light scattering (DLS) and UV–vis spectroscopy studies. The effect of UV light and temperature on the vesicles structure by SAXS and WAXS conducted on real time is also presented. Finally, the potential use of the vesicles to load and stimuli controlled release of small fluorescent molecules is probed.